2021
DOI: 10.1186/s12889-021-10453-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and physiological stress and burnout among maternity providers in a rural county in Kenya: individual and situational predictors

Abstract: Background Stress and burnout among healthcare workers has been recognized as a global crisis needing urgent attention. Yet few studies have examined stress and burnout among healthcare providers in sub-Saharan Africa, and even fewer among maternity providers who work under very stressful conditions. To address these gaps, we examined self-reported stress and burnout levels as well as stress-related physiologic measures of these providers, along with their potential predictors. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 87 publications
(62 reference statements)
6
51
1
Order By: Relevance
“…The findings are in line with findings of Francis, Robbins, and Wulff (2013) that conducted a study with Presbyterian Church (USA) pastors using Emotional Exhaustion in Ministry Scale and found that female pastors had significantly higher levels of emotional exhaustion and depersonalization than male pastors. Furthermore, the findings resonate with findings of Afulani et al (2021) who found that Female providers' scored high scores of emotion exhaustion compared to male providers. Catholic religious women experiencing more emotional exhaustion than religious men could be attributed to the nature of their ministry.…”
Section: Discussionsupporting
confidence: 78%
“…The findings are in line with findings of Francis, Robbins, and Wulff (2013) that conducted a study with Presbyterian Church (USA) pastors using Emotional Exhaustion in Ministry Scale and found that female pastors had significantly higher levels of emotional exhaustion and depersonalization than male pastors. Furthermore, the findings resonate with findings of Afulani et al (2021) who found that Female providers' scored high scores of emotion exhaustion compared to male providers. Catholic religious women experiencing more emotional exhaustion than religious men could be attributed to the nature of their ministry.…”
Section: Discussionsupporting
confidence: 78%
“…Several researchers have reported that female nurses generally have worse sleep problems than do male nurses [ 9 , 10 ]. Additionally, compared to male healthcare providers, female healthcare providers had higher burnout scores and a greater workload when they attempted to seek a work-life balance [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the influence of shift work and sleep disturbances on HRV and autonomic function has been an active area of investigation [ 27 ]. Afulani et al [ 11 ] investigated the relationship between HRV and sociodemographic factors among healthcare workers. Afulani’s study found single health providers and those with higher income had higher HRV than did clinical providers who were married and those with lower income, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the growing epidemic of mental health-related issues among healthcare workers, such as anxiety, burnout, depression, and substance abuse, confirm the challenges they are experiencing [1][2][3][4][5] . In comparison, there is a dearth of research on healthcare workers' positive mental health aspects such as happiness, especially in low-and middle-income countries 1,2 .…”
Section: Introductionmentioning
confidence: 99%